Effectiveness of English Online Learning Strategies During the Covid Pandemic at SMP Muhammadiyah 10 Sidoarjo - Danti Fadiah Syarafina (International Consortium of Education and Culture Research Studies, 2021)
The purposes of this research are analyze the effectiveness of online learning strategies used during teaching and learning activities and analyze the obstacles experienced during online teaching and learning activities. The research method used is qualitative descriptive research. Qualitative research is a research that is descriptive and describes the object of research/events studied and using analysis. The research results were obtained through extracting data through interview, observation, and documentation. Some data will be loaded in the form of diagram to show the research results obtained. The conclusion obtained is that this research is a descriptive qualitative research which aims to describe the learning strategies at Muhammadiyah 10 Junior High School Sidoarjo in English subject during the Covid-19 pandemic.